Recent Advances in Monitoring Technologies for Cardiac Troponin I: A Pivotal Biomarker in Cardiovascular Diseases - Ning Zhang; Yusong Wang; Fachuang Li; Yuxin Zhu; Zheng Fu; Mengda Jia; Xiaoran Zhan; Wanqing Zhang (Biomolecules, 2025)
Cardiovascular diseases (CVDs) are among the leading causes of morbidity and mortality rates globally, presenting a severe threat to human health and life. Acute myocardial infarction (AMI) is one of the most common and extremely severe disorders within CVDs, causing an estimated 17.5 million deaths each year. Cardiac troponin I (cTnI) is considered a biomarker for myocardial infarction and a “gold standard” method for diagnosing AMI due to its high specificity and sensitivity. The ability to rapidly detect cTnI with high sensitivity is critical throughout the diagnosis and treatment process of AMI. It is a necessary precursor for doctors to quickly assess the disease and initiate subsequent therapies. This work comprehensively explores various techniques for the analysis and detection of cTnI. We systematically review current cutting-edge technologies used for cTnI detection. According to optical, electrical, and intelligent technology dimensions, this study meticulously classifies and elaborates on the research progress of related sensors. Based on current research findings and technological development trends, we further project the future research directions and application prospects of cTnI sensors. This is geared towards providing valuable references for the further development of this field.